Productive Waqf Model Sustains Burial Funding: Evidence from Firdaus Memorial Park, Indonesia - Sudisto; Nurodin; Amelia Fauzia; Rizqi Handayani (Journal of Islamic Economics and Finance Studies, 2026)
The cemetery land crisis, minimal operational costs of public cemeteries, high cost of commercial cemeteries, and the suboptimal utilization of productive waqf have become obstacles in cemetery management in Indonesia. This study asks how Firdaus Memorial Park's (FMP) productive waqf model responds to these obstacles and argues that sustainability depends on fund separation, diversified productive investment, and a phased shift from capital accumulation to benefit distribution. This study employs a qualitative case study design with 11 informants (managers, waqifs, and community members) and data from interviews, internal documents, observation, and media. The findings reveal three main innovations of FMP. First, FMP separates waqf principal (IDR 25 million) from operational funds (IDR 5 million), with the principal invested across 12 diversified business units generating an 8.13% return, exceeding the 6% target. Second, FMP develops a two-phase model: a 10-12 years accumulation phase with 50% investment allocation to build capital until reaching IDR 56.7 billion, then transitioning to a sustainability phase with investment allocation dropping to 0.5% and cemetery allocation rising to 58%. Third, FMP achieves healthy financial sustainability with an ACR of 122.81%, 142% growth in waqf returns, a distribution ratio of 70.3% (exceeding the 50% requirement), and an 85% increase in beneficiaries. These mechanisms address operational funding, affordability, and the suboptimal use of productive waqf, while land scarcity is only partially addressed through efficient land use. The findings show that productive waqf can support sustainable burial funding without government subsidies while offering free services for the poor.   Krisis lahan pemakaman, minimnya biaya operasional TPU, mahalnya pemakaman komersial, dan belum optimalnya wakaf produktif menjadi kendala dalam pengelolaan pemakaman di Indonesia. Penelitian ini mempertanyakan bagaimana model wakaf produktif Firdaus Memorial Park (FMP) merespons kendala tersebut dan berargumen bahwa keberlanjutannya bergantung pada pemisahan dana, diversifikasi investasi produktif, serta peralihan bertahap dari akumulasi modal menuju distribusi manfaat. Penelitian ini menggunakan desain studi kasus kualitatif dengan 11 informan (pengelola, wakif, dan masyarakat) serta data dari wawancara, dokumen internal, observasi, dan media. Hasil penelitian menemukan tiga inovasi utama FMP. Pertama, FMP memisahkan pokok wakaf (Rp25 juta) dari dana operasional (Rp5 juta), dengan pokok diinvestasikan ke 12 unit bisnis yang menghasilkan return 8,13% melampaui target 6%. Kedua, FMP mengembangkan model dua-fase: fase akumulasi 10-12 tahun dengan alokasi investasi 50% untuk membangun modal hingga Rp56,7 miliar, kemudian bertransisi ke fase keberlanjutan dengan alokasi investasi turun menjadi 0,5% dan alokasi pemakaman naik menjadi 58%. Ketiga, FMP mencapai keberlanjutan finansial sehat dengan ACR 122,81%, pertumbuhan hasil wakaf 142%, rasio penyaluran 70,3% (melebihi ketentuan 50%), dan peningkatan penerima manfaat 85%. Mekanisme tersebut menjawab kendala pendanaan operasional, keterjangkauan, dan belum optimalnya wakaf produktif, sedangkan kelangkaan lahan baru dijawab secara parsial melalui efisiensi penggunaan lahan. Temuan ini menunjukkan bahwa wakaf produktif dapat mendukung pendanaan pemakaman berkelanjutan tanpa subsidi pemerintah sekaligus menyediakan layanan gratis bagi masyarakat miskin.